Bibliometric and visual analysis of membranous nephropathy literature from 2010 to 2023 - Chen, Yirui; Liu, Chen; Shen, Hongnan; Su, Pingping; Pang, Liang; Zeng, Congcong; Cheng, Jinguo (Frontiers in Pharmacology, 2024)
Background: Membranous glomerulonephritis, also known as membranous nephropathy (MN), is a common cause of nephrotic syndrome in adults. Despite extensive research on MN, bibliometric studies on the subject are scarce. Therefore, this study aimed to provide a visual analysis of global trends in membranous nephropathy research over the past 13 years. Methods: This study conducted a bibliometric and visual analysis of global trends in MN research from 2010 to 2023. Articles related to MN were retrieved from the Web of Science Core Collection (WoSCC) database. Tools such as CiteSpace and VOSviewer were utilized to analyze publications, countries, institutions, authors, publishing journals, co-cited references, and keywords to identify the current state and future trends in MN research. Results: The analysis encompassed 1,624 publications, showing an annual increase from 2010 to 2023. The People's Republic of China emerged as the most active country in this field, while